The Parental Role in Supporting Learners With Barriers to Learning in a Secondary School - Zinhle Thobeka Fakude; Nonhlanhla Desiree Maseko (Studies in Learning and Teaching, 2024)
Parental role in secondary schools is pivotal to support learners with barriers to learning to enhance their academic performance. Research indicates that parental involvement in leaners’ education decline as learners grow older. Therefore, the study aim was to explore the role of parents in supporting learners with barriers to learning in a secondary school. The research study was set within an interpretivism paradigm and used the qualitative approach. Epstein’s model for parental involvement was adopted in the study to explore the parental role in supporting learners with barriers to learning in a secondary school. The model emphasizes the involvement of parents in learners’ education in schools. The research is a niche as it covers a gap in secondary school where there is insufficient scholarly exploring parental involvement. Data was collected from purposefully sampled participants including parents of learners with barriers to learning, teachers who are teaching learners with barriers to learning and three learners with barriers to learning, through interviews. The thematic data analysis was used to analyze interviews data and document analysis. The findings from the study indicated that parents are keen to play their role in supporting learners with barriers to learning in a secondary school. However, parents are faced with different challenges that hinder their full engagement in supporting learners with barriers to learning. The study recommends that parents should continuously communicate and engage with school on how they can be assisted in supporting learners with barriers to learning at home. The study also recommends that the school should work hand in hand with parents providing guidance on how learners with barriers to learning should be supported at home.